Arabidopsis thaliana Leaf Epidermal Guard Cells: A Model for Studying Chloroplast Proliferation and Partitioning in Plants - Fujiwara, Makoto T.; Sanjaya, Alvin; Itoh, Ryuuichi D. (Frontiers in Plant Science, 2019)
The existence of numerous chloroplasts in photosynthetic cells is a general feature of plants. Chloroplast biogenesis and inheritance involve two distinct mechanisms: proliferation of chloroplasts by binary fission, and partitioning of chloroplasts into daughter cells during cell division. The mechanism of chloroplast number coordination in a given cell type is a fundamental question. Stomatal guard cells (GCs) in the plant shoot epidermis generally contain several to tens of chloroplasts per cell. Thus far, chloroplast number at the stomatal (GC-pair) level has generally been used as a convenient marker for identifying hybrid species or estimating the ploidy level of a given plant tissue. Here, we report that Arabidopsis thaliana leaf GCs represent a useful system for investigating the unexploited aspects of chloroplast number control in plant cells. In contrast to a general notion based on analyses of leaf mesophyll chloroplasts, a small difference was detected in the GC chloroplast number among three Arabidopsis ecotypes (Columbia, Landsberg erecta, and Wassilewskija). Fluorescence microscopy often detected dividing GC chloroplasts with the FtsZ1 ring not only at the early stage of leaf expansion but also at the late stage. Compensatory chloroplast expansion, a phenomenon well documented in leaf mesophyll cells of chloroplast division mutants and transgenic plants, could take place between paired GCs in wild-type leaves. Furthermore, modest chloroplast number per GC as well as symmetric division of guard mother cells for GC formation suggest that Arabidopsis GCs would facilitate the analysis of chloroplast partitioning, based on chloroplast counting at the individual cell level.